2002
DOI: 10.1088/1126-6708/2002/10/069
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Strings in Confining AdS/CFT Backgrounds

Abstract: We study semiclassical rotating strings in AdS/CFT backgrounds that exhibit both confinement and finite-size effects. The energy versus spin dispersion relation for short strings is the expected Regge trajectory behaviour, with the same string tension as is measured by the Wilson loop. Long strings probe the interplay between confinement and finite-size effects. In particular, the dispersion relation for long strings shows a characteristic dependence on the string tension and the finite-size scale.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Then, using (3.5), we find that the energy E and the angular momentum J β are related by the Regge relation 8) corresponding to the string tension (2.4). This relation was pointed out in this context in [19]. For a string with a generic integer ω = 1, the energy formula (3.8) is multiplied by a factor √ ω.…”
Section: Glueball States and The Regge Stringmentioning
confidence: 86%
See 2 more Smart Citations
“…Then, using (3.5), we find that the energy E and the angular momentum J β are related by the Regge relation 8) corresponding to the string tension (2.4). This relation was pointed out in this context in [19]. For a string with a generic integer ω = 1, the energy formula (3.8) is multiplied by a factor √ ω.…”
Section: Glueball States and The Regge Stringmentioning
confidence: 86%
“…1 Previous discussions on semiclassical string solutions in this model are in [19,20]. Studies of semiclassical string solutions in other confining backgrounds can be found in [21].…”
Section: Qcd 3+1 Model: Generalities and Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The semiclassical approach is also expected to hold for more general cases such as nonor less supersymmetric cases and non-conformal cases [18,14,19,20,21,22,23]. The orbiting strings in a AdS 5 black hole background have been investigated and associated with the glueball states in the dual finite temperature N =4 SYM theory [18].…”
Section: Introductionmentioning
confidence: 99%
“…Rotating string configurations in a confining geometry produced by an AdS charged black hole have been also studied [19], where long strings probe the interplay between confinement and finite-size effect. Further in Witten's model for QCD constructed with near-extremal Dp-branes the string configurations rotating along a circle with a fixed radius in the non-compact directions of Dp-branes, have been shown to give the dispersion relations between the energy and the linear momentum along the compact circle [19,20]. The semiclassical approach has been applied to the membranes rotating in the G 2 holonomy backgrounds that are not AdS × Stype ones and dual to N =1 gauge theories in four dimensions and various type of energy-spin relations have been presented [21], while several folded closed string configurations have been studied in the Maldacena-Nuñez background, dual in the infra-red to N =1 gauge theories in four dimensions [23].…”
Section: Introductionmentioning
confidence: 99%